6(n+3)=0

Simple and best practice solution for 6(n+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(n+3)=0 equation:


Simplifying
6(n + 3) = 0

Reorder the terms:
6(3 + n) = 0
(3 * 6 + n * 6) = 0
(18 + 6n) = 0

Solving
18 + 6n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + 6n = 0 + -18

Combine like terms: 18 + -18 = 0
0 + 6n = 0 + -18
6n = 0 + -18

Combine like terms: 0 + -18 = -18
6n = -18

Divide each side by '6'.
n = -3

Simplifying
n = -3

See similar equations:

| (r-2)(r+10)=9 | | 2x-13=x+41 | | -4(4n+2)=20 | | 8-4x=15-5x | | 3(3g+40)-9g-120=0 | | 2x-40=x-20 | | 0.8x-0.3(50+x)=0.2(50) | | (x-2y)dx+(2x+y)dy=0de | | y=2x^2+kx+4 | | Q=60-4Pforp | | 5t^2+4t=0 | | 5=-3n+4n | | 3x+8=12X | | 9=3x-8 | | S=7x^2y | | h+(2h-1000)=440 | | c/12=5 | | z+4=69 | | 24x^3-15x^2+8x-5= | | 4z-2-(1-z)=4 | | 3+9(x-4)=8-8(x-7) | | =(4x+3)(4x-3) | | (-5a^3b^3)(6ab^5)= | | 13-x=209 | | a-17=18 | | x+(2x+1000)=4400 | | 3(3k+5)-14k+8+5= | | 3x+17-x+17=-4 | | 10k+73=2(5k+34) | | x=2x^2-6 | | b=a+8 | | 4log(x-7)+4log(x-7)=1 |

Equations solver categories